The Implementation of Tilawati Method in Improving Quality of Reading Qur'an in Madrasah Ibtidaiyah (MI) Jakarta - Rumyati, Wahyu; Alwiyah, Lulu; Khumaeroh, Anisatul; Reksiana, Reksiana; Sari, Yeasy Agustina (Tapis: Jurnal Penelitian Ilmiah, 2021)
Many people find it difficult to read the Qur'an, be it from children, teenagers, parents, from both men and women. When in fact the Qur'an is easy to learn and not difficult, provided that there is a will, seriousness and sincerity in studying it. The article aimed to find out how the tilawati method improve the students’ quality of Reading Qur’an. This study was a qualitative descriptive analysis with a research background at Madrasah Ibtidaiyah (MI) Pembangunan Jakarta. Researchers made observations on the quality of students' reading of the Qur'an in learning, which included students' reading fluency, the ability to read the Qur'an using the correct rules of recitation law, and the ability to read and pronounce the letters according to their makhraj. The result show that The application of the Tilawati method in learning the Qur'an at Madrasah Ibtidaiyah (MI) The development of Jakarta is in accordance with the rules that have been mutually agreed upon by the Tilawati institution. The application of the Tilawati method is carried out in several stages, such as opening activities, core activities and closing activities. Keywords: : Quality Reading Qur’an, Tilawati Method, Reading Qur’an